The Influence of Organizational Justice Dimensions on Affective Commitment and Employees Counterproductive Behavior - Muhammad Zakiy; Muhsin Hariyanto (IJHCM (International Journal of Human Capital Management), 2022)
Employees' work dynamics in companies are very diverse. Some employees have high commitments, and others are very low. Likewise, the counterproductive behavior of employees in every company is also high or low. The importance of the two factors for the continuity of company operations incites the investigation to ponder the role of the dimensions of justice on affective commitment and counterproductive work behavior of employees in Islamic Financial Institutions (LKS) in DIY. Researchers distributed questionnaires to 219 employees from several LKS in DIY with purposive sampling. The data were then analyzed through SEM-PLS, which measures the research instrument and the influence between the research variables. The results of this study indicated that only procedural and interactional justice trigger affective commitment and deviant workplace behavior, while distributive justice is unable to influence these two variables. The study contributed to LKS managers maintaining a work environment that upholds the principles of justice to increase affective commitment and minimize employees' deviant behavior.